yâ€™=\frac{ay+bx}{cy+dx }.

idontknow Dec 2015 972 128 Earth Nov 10, 2019 #2 My approach: \(\displaystyle y=xs \; \) , \(\displaystyle (xs)â€™=\frac{as+b}{cs+d}\). \(\displaystyle xsâ€™ =\frac{as+b}{cs+d }-s\) or \(\displaystyle \int dx/x=\int [\frac{as+b}{cs+d }-s]^{-1}ds\).

My approach: \(\displaystyle y=xs \; \) , \(\displaystyle (xs)â€™=\frac{as+b}{cs+d}\). \(\displaystyle xsâ€™ =\frac{as+b}{cs+d }-s\) or \(\displaystyle \int dx/x=\int [\frac{as+b}{cs+d }-s]^{-1}ds\).

V v8archie Math Team Dec 2013 7,709 2,677 Colombia Nov 10, 2019 #3 It's a standard homogeneous form. You solution is standard. Reactions: 2 people